Complex associations between anxiety, depression, and resilience in a college student sample: a network analysis - Wang, Hui; Wang, Min; Wang, Xiuchao; Feng, Tingwei; Liu, Xufeng; Xiao, Wei (Frontiers in Psychiatry, 2025)
BackgroundAnxiety and depression have significant impacts on individuals’ mental health and social functioning, particularly among college students. Psychological resilience is considered a crucial resource for coping with adversity and stress and may play a key role in alleviating anxiety and depression symptoms. The aim of this study is to explore the finer-grained potential relationships between psychological resilience, anxiety, and depression among college students.MethodsThis study employed network analysis to examine the psychological resilience, anxiety, and depression status of a randomly sampled cohort of 855 college students (51.8% female; M = 18.70, SD = 1.13). Statistical analyses and network visualization were conducted using R version 4.2.2 and the qgraph package. Bridge centrality indices of variables within the network were computed, with particular emphasis on the significance of bridge symptoms within the network structure.ResultsSignificant covariation was observed between anxiety and depression symptoms. Psychological resilience exhibited a negative correlation with both anxiety and depression, with a negative bridge expected influence value for R10 “Can handle unpleasant feelings”, indicating a potential protective role of psychological resilience in mitigating these mental health issues. R10 “Can handle unpleasant feelings” occupies the most central position within the psychological resilience network, with the smallest BEI value (-0.01), indicating its protective role in the overall network. To some extent, it can regulate anxiety and depression symptoms.ConclusionThis study highlights the complex interrelationships between psychological resilience, anxiety, and depression among college students through network analysis. Bridge expected influence analysis identified “R10” as a protective factor and “A7” as a key risk factor. The findings suggest that interventions targeting bridge symptoms and enhancing resilience may help alleviate anxiety and depression. Prioritizing these two symptoms in future research could yield greater intervention benefits.